Touching Up Mental Rotation: Effects of Manual Experience on 6‐Month‐Old Infants' Mental Object Rotation. Issue 5 (24th February 2013) - Möhring, Wenke; Frick, Andrea
Abstract : In this study, 6‐month‐olds' ability to mentally rotate objects was investigated using the violation‐of‐expectation paradigm. Forty infants watched an asymmetric object being moved straight down behind an occluder. When the occluder was lowered, it revealed the original object (possible) or its mirror image (impossible) in one of five orientations. Whereas half of the infants were allowed to manually explore the object prior to testing, the other half was only allowed to observe the object. Results showed that infants with prior hands‐on experience looked significantly longer at the mirror image, while infants with observational experience did not discriminate between test events. These findings demonstrate that 6‐month‐olds' mental rotations benefit from manual exploration, highlighting the importance of motor experience for cognitive performance.